PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP PRICE TO BOOK VALUE DENGAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Sektor Industri Barang Konsumsi di Bursa Efek Indonesia Periode 2013-2017) - Ratna Aprilia Setia Rini; Zarah Puspitaningtyas; Aryo Prakoso (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The most famous main objective of a company is to increase the prosperity of the owner or shareholder by increasing the company value. The researchers used price to book value as the measurement indicator of company value. One of the factors influencing the high and the low value of the company is the company's financial performance as reflected in the company's financial statement with focus on current ratio, total asset turnover, debt to equity ratio, and return on asset as intervening variable. The object of this study was 18 industrial consumer goods companies listed in the Indonesia Stock Exchange. The data were analyzed by using path analysis. Based on the result of data analysis, it was obtained that current ratio and total asset turnover affected significantly on price to book value. On the contrary, debt to equity ratio and return on asset did not affect significantly on price to book value. Current ratio and total asset turnover affected significantly on price to book value with return on asset as the intervening variable. Conversely, debt to equity ratio did not affect significantly on price to book value with return on asset as the intervening variable. Keywords: current ratio, total asset turnover, debt to equity ratio, return on asset, price to book value